2017
DOI: 10.1155/2017/1697018
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Reduces Ischemia‐Induced Kidney Mitochondrial Injury in Rats

Abstract: During partial nephrectomy, the avoidance of ischemic renal damage is extremely important as duration of renal artery clamping (i.e., ischemia) influences postoperative kidney function. Mitochondria (main producer of ATP in the cell) are very sensitive to ischemia and undergo damage during oxidative stress. Finding of a compound which diminishes ischemic injury to kidney is of great importance. Caffeic acid phenethyl ester (CAPE), biologically active compound of propolis, might be one of the promising therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…It was also demonstrated by Feng et al that CAPE and its related phenolic compounds could protect the efficiency of oxidative phosphorylation (state 3 increased and state 4 decreased), as shown by the ADP/O ratio [ 48 ]. This is in agreement with our data and with our previous data from an in vitro kidney ischemia model [ 2 ] that showed an increase in the mitochondrial state 3 respiration (V ADP ) with glutamate/malate after pretreatment with two doses of CAPE (22 mg/kg and 34 mg/kg) as compared with the untreated group (ischemia/reperfusion).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was also demonstrated by Feng et al that CAPE and its related phenolic compounds could protect the efficiency of oxidative phosphorylation (state 3 increased and state 4 decreased), as shown by the ADP/O ratio [ 48 ]. This is in agreement with our data and with our previous data from an in vitro kidney ischemia model [ 2 ] that showed an increase in the mitochondrial state 3 respiration (V ADP ) with glutamate/malate after pretreatment with two doses of CAPE (22 mg/kg and 34 mg/kg) as compared with the untreated group (ischemia/reperfusion).…”
Section: Discussionsupporting
confidence: 93%
“…Our recent in vitro study [ 2 ] has revealed that CAPE has a positive effect against ischemia-induced injury, namely that it partially protected rat kidney mitochondria from in vitro ischemia-induced damage. Since most studies, including our own, have been performed in vitro [ 2 ], the question remains open as to whether the same results will be observed in in vivo experiments. Such studies in kidney mitochondria have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other previous studies have noted that phenolic acid and ester compounds play a positive role in amending lipid metabolism. For example, several studies have shown that CAPE has antioxidant, anti-inflammatory, and cytostatic properties and hepatorenal protective effects against the cytotoxic injuries linked to metabolic syndrome and vascular diseases [42][43][44][45]. CAPE can also reduce the activation of the nuclear factor κB pathway in high-fat diet-induced obesity mice [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial oxygen consumption rates was measured using Oroboros oxygraph-2 k in 2 mL incubation medium containing 10 mM Tris·Cl, 5 mM KH 2 PO4, 150 mM KCl, 1 mM MgCl 2 × 6H 2 O, pH 7.2, 37°C with 5 mM glutamate + 5 mM malate, or 15 mM succinate + 2 mM amytal (an inhibitor of complex I) as respiratory substrates. All experimental conditions are described in [ 10 ]. The mitochondrial routine respiration rate ( V 0 ) was recorded in the medium supplemented with mitochondria and substrates (complex I-dependent substrate: glutamate 5 mM + malate 5 mM, or complex II-dependent substrate: succinate 15 mM + 2 mM amytal as complex I inhibitor); original curves of mitochondrial respiration are seen in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%